Sie sind auf Seite 1von 6

ID : F-6-Fractions-Reducing-them-to-the-simplest-form [1]

Grade 6 Fractions - Reducing them to the simplest form

For more such worksheets visit www.EduGain.com

Fill in the blanks

(1)

Solve the following and reduce to the simplest form:

A)

D)

G)

J)

M)

(

2

2

5

÷

1

4

5

)

(

2

2

3

÷

2

2

3

)

(

1

=

1

11

÷

1

7

11

1 1

(

1

÷

1

)

2 2

(

1

1

3

÷

2

1

3

)

+

+

+

+

3

2

) +

2

3

4 B)

=

(

3

3

÷ 2

5 5

=

4

5

2 E)

3

3

=

9

11

H)

1 K)

2

=

1 1

(

2

÷ 2

2 2

=

(

=

2

3

5

÷ 3

4

5

2 1

(

1

÷ 1

3 3

=

1 N)

3

=

1 1

(

1

÷ 1

2 2

=

)

)

)

)

)

+

+

+

+

+

2

1

2

3

2

4

5

1

2

4

5

1

3

1

2

C)

F)

I)

L)

O)

1 1

(

1

÷ 1

2 2

=

2 2

(

2

÷ 2

3 3

=

(

=

2

1

5

÷ 2

1

5

1 1

(

2

÷ 2

2 2

=

4 1

(

1

÷ 1

5 5

=

)

)

)

)

)

+

+

+

+

+

1

1

3

2

3

1

2

1

3

1

5

1

2

2

5

Many more such worksheets can be generated at www.EduGain.com

(C) 2015 EduGain (www.EduGain.com)

Personal use only, commercial use is strictly prohibitated

(1)

A)

 77 15 Step 1 2 4 ( 2 ÷ 1 ) + 5 5 4 3 can be written 5 as: 2 4 ( 2 ÷ 1 ) + 5 5 4 12 9 3 = ( ÷ ) 5 5 5 19 + 5 12 5 19 = ( × ) + 5 9 5 12 19 = + 9 5 60 + 171 = 45 231 = 45 77 = 15 Step 2 Now the simplest form 2 4 of ( 2 ÷ 1 ) + 5 5 4 77 3 is . 5 15

D)

11
3

B)

E)

(C) 2015 EduGain (www.EduGain.com)

ID : F-6-Fractions-Reducing-them-to-the-simplest-form [2]

 143 35 Step 1 3 4 ( 3 ÷ 2 ) + 5 5 4 2 can be written 5 as: 3 4 ( 3 ÷ 2 ) + 5 5 4 18 14 2 = ( ÷ 5 5 5 14 ) + 5 18 5 = ( × ) + 5 14 14 5 18 14 = + 14 5 90 + 196 = 70 286 = 70 143 = 35 Step 2 Now the simplest 3 form of ( 3 ÷ 5 4 4 2 ) + 2 is 5 5 143 . 35
5
2

C)

F)

 5 2 Step 1 1 1 ( 1 ÷ 1 ) + 2 2 1 1 can be written 2 as: 1 1 ( 1 ÷ 1 ) + 2 2 1 3 3 1 = ( ÷ ) 2 2 2 3 + 2 3 2 3 = ( × ) + 2 3 2 3 3 = + 3 2 6 + 9 = 6 15 = 6 5 = 2 Step 2 Now the simplest 1 form of ( 1 ÷ 2 1 1 5 1 ) + 1 is 2 2 2 . 7 3

Personal use only, commercial use is strictly prohibitated

G)

 Step 1 2 2 ( 2 ÷ 2 ) + 3 3 2 2 can be written 3 as: 2 2 ( 2 ÷ 2 ) + 3 3 2 8 8 2 = ( ÷ ) + 3 3 3 8 3 8 3 8 = ( × ) + 3 8 3 8 8 = + 8 3 24 + 64 = 24 88 = 24 11 = 3 Step 2 Now the simplest form 2 2 of ( 2 ÷ 2 ) + 3 3 2 11 2 is . 3 3 148 33 Step 1 1 7 ( 1 ÷ 1 ) + 11 11 9 3 can be written 11 as:

H)

(C) 2015 EduGain (www.EduGain.com)

ID : F-6-Fractions-Reducing-them-to-the-simplest-form [3]

 Step 1 1 1 ( 2 ÷ 2 ) + 2 2 1 1 can be written 2 as: 1 1 ( 2 ÷ 2 ) + 2 2 1 5 5 1 = ( ÷ ) 2 2 2 3 + 2 5 2 3 = ( × ) + 2 5 2 5 3 = + 5 2 10 + 15 = 10 25 = 10 5 = 2 Step 2 Now the simplest 1 form of ( 2 ÷ 2 1 1 5 2 ) + 1 is 2 2 2 . 331 95 Step 1 3 4 ( 2 ÷ 3 ) + 5 5 4 2 can be written 5 as:

I)

 Step 1 2 2 ( 2 ÷ 2 ) + 3 3 1 1 can be written 3 as: 2 2 ( 2 ÷ 2 ) + 3 3 1 8 8 1 = ( ÷ ) 3 3 3 4 + 3 8 3 4 = ( × ) + 3 8 3 8 4 = + 8 3 24 + 32 = 24 56 = 24 7 = 3 Step 2 Now the simplest 2 form of ( 2 ÷ 3 2 1 7 2 ) + 1 is 3 3 3 . 21 5 Step 1 1 1 ( 2 ÷ 2 ) + 5 5 1 3 can be written 5 as:

Personal use only, commercial use is strictly prohibitated

J)

 1 7 ( 1 ÷ 1 ) + 11 11 9 12 18 3 = ( ÷ 11 11 11 42 ) + 11 12 11 42 = ( × ) + 11 18 11 12 42 = + 18 11 = 132 + 756 198 888 = 198 148 = 33 Step 2 Now the simplest form 1 7 of ( 1 ÷ 1 ) 11 11 9 148 + 3 is . 11 33 7 2 Step 1 1 1 ( 1 ÷ 1 ) + 2 2 1 2 can be written 2 as: 1 1 ( 1 ÷ 1 ) + 2 2

K)

(C) 2015 EduGain (www.EduGain.com)

ID : F-6-Fractions-Reducing-them-to-the-simplest-form [4]

 3 4 ( 2 ÷ 3 ) + 5 5 4 13 19 2 = ( ÷ 5 5 5 14 ) + 5 13 5 = ( × ) + 5 19 14 5 13 14 = + 19 5 65 + 266 = 95 331 = 95 Step 2 Now the simplest 3 form of ( 2 ÷ 5 4 4 3 ) + 2 is 5 5 331 . 95 55 12 Step 1 2 1 ( 1 ÷ 1 ) + 3 3 1 3 can be written 3 as: 2 1 ( 1 ÷ 1 ) + 3 3

L)

 1 1 ( 2 ÷ 2 ) + 5 5 1 11 11 3 = ( ÷ 5 5 5 16 ) + 5 11 5 = ( × ) + 5 11 16 5 11 16 = + 11 5 55 + 176 = 55 231 = 55 21 = 5 Step 2 Now the simplest 1 form of ( 2 ÷ 5 1 1 2 ) + 3 is 5 5 21 . 5 7 2 Step 1 1 1 ( 2 ÷ 2 ) + 2 2 1 2 can be written 2 as: 1 1 ( 2 ÷ 2 ) + 2 2

Personal use only, commercial use is strictly prohibitated

M)

 1 3 3 2 = ( ÷ ) + 2 2 2 5 2 3 2 5 = ( × ) + 2 3 2 3 5 = + 3 2 6 + 15 = 6 21 = 6 7 = 2 Step 2 Now the simplest form 1 1 of ( 1 ÷ 1 ) + 2 2 1 7 2 is . 2 2 82 21 Step 1 1 1 ( 1 ÷ 2 ) + 3 3 1 3 can be written 3 as: 1 1 ( 1 ÷ 2 ) + 3 3 1 4 7 3 = ( ÷ ) + 3 3 3 10 3 4 3 10 = ( × ) + 3 7 3

N)

(C) 2015 EduGain (www.EduGain.com)

ID : F-6-Fractions-Reducing-them-to-the-simplest-form [5]

 1 5 4 3 = ( ÷ ) 3 3 3 10 + 3 5 3 10 = ( × ) + 3 4 3 5 10 = + 4 3 15 + 40 = 12 55 = 12 Step 2 Now the simplest 2 form of ( 1 ÷ 3 1 1 1 ) + 3 is 3 3 55 . 12 7 2 Step 1 1 1 ( 1 ÷ 1 ) + 2 2 1 2 can be written 2 as: 1 1 ( 1 ÷ 1 ) + 2 2 1 3 3 2 = ( ÷ ) 2 2 2 5 + 2 3 2 5 = ( × ) + 2 3 2

O)

 1 5 5 2 = ( ÷ ) 2 2 2 5 + 2 5 2 5 = ( × ) + 2 5 2 5 5 = + 5 2 10 + 25 = 10 35 = 10 7 = 2 Step 2 Now the simplest 1 form of ( 2 ÷ 2 1 1 7 2 ) + 2 is 2 2 2 . 49 10 Step 1 4 1 ( 1 ÷ 1 ) + 5 5 2 3 can be written 5 as: 4 1 ( 1 ÷ 1 ) + 5 5 2 9 6 3 = ( ÷ ) 5 5 5 17 + 5 9 5 17 = ( × ) + 5 6 5

Personal use only, commercial use is strictly prohibitated

4
10
=
+
7
3
12 + 70
=
21
82
=
21
Step 2
Now the simplest form
1 1
of (
÷
) +
1
2
3
3
1
82
is
.
3
3
21

(C) 2015 EduGain (www.EduGain.com)

ID : F-6-Fractions-Reducing-them-to-the-simplest-form [6]

 3 5 = + 3 2 6 + 15 = 6 21 = 6 7 = 2

Step 2

Now the simplest

.

1

2

1 1

2 2

7

2

form of (

1

÷

1

) +

2

is

9
17
=
+
6
5
45 + 102
=
30
147
=
30
49
=
10
Step 2
Now the simplest
4
5
1 2
5 5
49
.
10

form of (

1

÷

1

) +

3

is

Personal use only, commercial use is strictly prohibitated